Intracellular Self‐Assembly of Nanoprobes for Molecular Imaging. Issue 8 (20th June 2018) - Hai, Zijuan; Liang, Gaolin
Abstract: Molecular imaging can be roughly defined as the characterization and measurement of biological processes at the molecular and cellular level. Nanoprobes (NPs) are advantageous over small molecular probes for molecular imaging in the amount of signaling molecule as well as signal intensity. Compared with ex situ self‐assembling strategies for NP fabrication, those intracellular intelligent self‐assembling strategies that use small molecules to prepare NPs in situ with amplified signals and longer retention time are more efficient and attractive. This review summarizes recent advances of intracellular self‐assembly of NPs for molecular imaging in five modalities (magnetic resonance imaging, computed tomography, radionuclide imaging, optical imaging, and photoacoustic imaging). Moreover, using intracellular self‐assembly strategies to fabricate NPs in situ for multimodality imaging in the future is outlooked in this review. Abstract : Intracellular self‐assembly for molecular imaging : Intracellular self‐assembly, which starts with a small molecule to translocate the cell membrane but ends up with nanostructures inside cells, is attractive for molecular imaging. Up to date, several intracellular self‐assembly systems have been successfully applied for molecular imaging in five modalities including magnetic resonance imaging, computed tomography, radionuclide imaging, optical imaging, and photoacoustic imaging.